China's effect on world energy-growth nexus: Spillovers evidence from financial development and CO₂ emissions - Luís Miguel Marques; José Alberto Fuinhas; António Cardoso Marques (Economies, 2021)
This paper aims to extend the literature on the impacts of China's policies on the world energy-growth nexus by analyzing the spillover effects of financial development and CO2 emissions. An autoregressive distributed lag approach was applied to annual series data from 1977 to 2016. Models for four world regions were developed, as well as a global model. The results reveal the traditional feedback hypothesis on the whole, both in the short- and long-run. Additionally, the results support that China's CO2 emission and financial development promote world energy consumption. In regard to the four world regions, heterogeneous results were observed. Overall, China's financial development and CO2 emissions also have heterogenous worldwide impacts with distinct magnitudes. Accordingly, no country should be indifferent to China's policies, and independence should be promoted for Europe, Central Asia and Asia Pacific aggregates.
Keywords: 330; CO2 emission; economic growth; energy consumption; financial development; spillover effects